The existence of Dodol Betawi in the post Covid-19 era: A case study - Solehudin, Rd. Heri; Gunawan, Rudy; Alamsyah, Taufik; Pohan, Ary Septanauli; Kaibama, Bustami M.; Brar, Balraj Singh (Harmoni Sosial: Jurnal Pendidikan IPS, 2023)
Dodol Betawi is a specialty food processed by the Betawi people and is one of the archipelago's culinary delights that should be preserved. Dodol Betawi is in great demand by the public, not only from the Betawi tribe of Jakarta but also from people in other regions. The Covid-19 pandemic has devastated the entire small home-based business sector, which is still conservative. In addition, the progress of modern times has also contributed to the decline in Dodol Betawi's competitiveness in the current culinary market. This research was conducted to find the strategy of traditional processed food amid increasingly competitive modern processed food business competition as a study material in developing local wisdom-based entrepreneurship. This research was conducted using qualitative methods through a case study approach. Data collection was done through observation and interviews. The sampling technique used was purposive sampling. Data analysis in this study was carried out through three stages: data reduction, data presentation, and conclusions. The results showed that Dodol Betawi, before the pandemic, was generally used for Betawi community celebrations. This is exacerbated by the competition of various types of processed foods sold online, making Bu Amsah's Dodol Betawi producers experience a drastic decline and even difficulty competing.